(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The optimum machining conditions recommended in the literature for one of the most commonly used materials for responsible heavy-duty workpieces in mechanical engineering, 42CrMo4+QT steel, are valid only for certain cutting tools and machine tools. This paper presents the results of an investigation of the machinability of this type of steel on the criteria of cutting tool lifetime and roughness of machined surfaces in turning on CNC machines with robotic power supply. A planned experiment has been carried out as a result of which theoretical and experimental models have been obtained and graphical dependencies, reflecting the influence of cutting speed and feed when working with replaceable carbide inserts from different manufacturers have been constructed. The dependencies allow to predict with sufficient accuracy the tool lifetime of the studied inserts and the roughness of the machined surfaces using cutting conditions in a certain range. The analysis carried out shows that the machinability of 42CrMo4+QT steel depends on the elements of the cutting conditions, with the widest variation in the values of the cutting tool lifetime criterion. The cutting speed has a stronger influence on this criterion. The optimum cutting conditions that guarantee maximum tool lifetimes of the studied inserts and minimum roughness of the machined surfaces ware determined.